Female Agency through Border-Crossing and Transformation in Native American Women’s Poems - Kristianto, Bayu (Celt: A Journal of Culture, English Language Teaching & Literature, 2022)
This paper analyzes two poems by indigenous women authors from America, Karenne Wood and Joy Harjo, centering on the deer image, “Deer Woman” and “Deer Dancer,” respectively. The deer image has certain significance for these authors and their communities, because deer were hunted to provide sustenance for their survival. In certain cases, in these communities, boundaries between the deer and the human could not be easily ascertained. The transformation of the deer into the human and vice-versa underscores the fluid boundaries of human relationships with other beings, as well as the power and agency that emanate from such transformation. Through a close reading of the two poems, analysis reveals a conception of female agency that centers on willing transformation and aims for complete union with another in the interest of community survival and well-being. These native women authors’ poetic representations of deer serve as a critique of female agency, which is usually and primarily defined from the perspective of Western feminists.